2014
DOI: 10.1115/1.4028885
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Economy of a Multimode Combustion Engine With Three-Way Catalytic Converter

Abstract: Highly diluted, low temperature homogeneous charge compression ignition (HCCI) com-bustion leads to ultralow levels of engine-out NOx emissions. A standard drive cycle, however, would require switches between HCCI and spark-ignited (SI) combustion modes. In this paper we quantify the efficiency benefits of such a multimode combustion engine, when emission constraints are to be met with a three-way catalytic converter (TWC). The TWC needs unoccupied oxygen storage sites in order to achieve acceptable performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…AFR should be kept close to stoichiometric for catalyst efficiency. Any leaning that occurs should be small relative to the catalyst oxygen storage capacity, as filling of the oxygen storage may affect the allowable stay duration in HCCI [18]. The SI-HCCI switch point should be reached as quickly as possible for fast entry to HCCI.…”
Section: Cam Switching Spark Ignition-homogeneous Charge Compression mentioning
confidence: 99%
“…AFR should be kept close to stoichiometric for catalyst efficiency. Any leaning that occurs should be small relative to the catalyst oxygen storage capacity, as filling of the oxygen storage may affect the allowable stay duration in HCCI [18]. The SI-HCCI switch point should be reached as quickly as possible for fast entry to HCCI.…”
Section: Cam Switching Spark Ignition-homogeneous Charge Compression mentioning
confidence: 99%
“…A comparable analysis in another engine with multimode combustion can also be found in Gao et al 25 concerning reactivity controlled compression ignition (RCCI) and conventional diesel combustion. In Nu¨esch et al, 26 the interaction between SI/HCCI multimode engine and three-way catalyst was analyzed in terms of drive cycle fuel economy and NO x emissions. It was shown that the catalyst's oxygen storage fills up and requires depletion and hence rich operation.…”
Section: Introductionmentioning
confidence: 99%
“…the feasible HCCI operating regime being an actual residence in HCCI combustion mode. Both [1,4] switch combustion modes based on the state of the three-way catalyst, thereby taking into account its temperature [1] and oxygen storage level [4]. The integration of a multimode combustion in a hybrid electric vehicle is discussed in [5,6] with a focus on the power and torque split decisions.…”
Section: Introductionmentioning
confidence: 99%